Direct Micropatterning of Phase Separation Membranes Using Hydrogel Soft Lithography. Issue 7 (12th March 2019) - Asad, Asad; Sadrzadeh, Mohtada; Sameoto, Dan
Abstract: In this work a novel method is presented to directly apply microscale patterns on the membrane surface using hydrogel facilitated phase separation (HFPS). The hydrogel mold initiates phase separation spontaneously when it contacts the polymer solution and this guarantees that location of the dense skin layer is on the patterned side. In this fashion, the active surface area of a membrane is larger than the equivalent flat surface and subsequently enhances water flux without changing the membrane surface chemistry. The morphological properties of the HFPS membranes show similarity to the nonsolvent induced phase separation ones; however, a pore enlarging is noticed in the HFPS membranes due to the slow demixing rate of the solvent/nonsolvent in the phase separation process. The permeation results show that the HFPS patterned membrane doubles the pure water permeate flux when compared to the HFPS unpatterned membrane. This increase is attributed to the combined effect of enhanced surface area and a slight increase in the average pore size of the membrane. Moreover, fouling experiments with bovine serum albumin solution show a 78% increment in the flux for the patterned membrane after 100 min of operation, demonstrating the advantage of using microstructured membrane for filtration applications. Abstract : A novel method to prepare micropatterned membranes using hydrogel molds is presented. The membrane has finger‐like asymmetric structures with a dense skin layer on the structured side. The increase in surface area leads to higher flux without sacrificing rejection. Hydrogel molding allows applying bioinspired structures on the membrane surface from synthetic (Figure a) or natural (Figure b) surfaces.